2023
DOI: 10.1108/jhom-05-2021-0181
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing innovative culture in a healthcare organisation – Lessons from a Swedish case study

Abstract: PurposeHealthcare organisations are often described as less innovative than other organisations, since organisational culture works against innovations. In this paper, the authors ask whether it has to be that way or whether is possible to nurture an innovative culture in a healthcare organisation. The aim of this paper is to describe and analyse nurturing an innovative culture within a healthcare organisation and how culture can support innovations in such a healthcare organisation.Design/methodology/approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
(186 reference statements)
1
4
0
Order By: Relevance
“…They have competitive abilities and help maintain the structure of the organization as a whole. Consistent with the study of Andersson et al (2023), it was found that entrepreneurs will achieve higher success if knowledge management is consistently put into practice to achieve the discovery of creativity to make the organization competitive. The study of Samie & Jazghani, (2022) found that organizational innovation can occur through knowledge management and knowledge sharing.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…They have competitive abilities and help maintain the structure of the organization as a whole. Consistent with the study of Andersson et al (2023), it was found that entrepreneurs will achieve higher success if knowledge management is consistently put into practice to achieve the discovery of creativity to make the organization competitive. The study of Samie & Jazghani, (2022) found that organizational innovation can occur through knowledge management and knowledge sharing.…”
Section: Discussionsupporting
confidence: 61%
“…For example, entrepreneurs allow employees to be free to work; giving employees the freedom to try and make errors. No strict rules set to allow employees to participate in creating innovations to occur in a sustainable organization (Andersson et. al., 2023).…”
Section: Innovative Organizationmentioning
confidence: 99%
“…Another area may be interior esthetics (Rashdan, Ashour, 2022). Design thinking is also commonly used to overcome cultural resistance to innovation in healthcare (Andersson et al, 2023).…”
Section: Practices Of Applying Design Thinking To Social Innovation A...mentioning
confidence: 99%
“…The ageing population and increasing prevalence of chronic diseases challenge resource allocation within healthcare systems and health-related sectors in general (Michel and Ecarnot, 2020; Pilleron et al ., 2021; Van Baarle et al ., 2020; Linnéusson et al ., 2022; Andersson et al ., 2023). A shift from the traditional paternalistic value delivery model (Sandman and Munthe, 2010) to a more patient-centred shared decision-making model (Elwyn et al ., 2012) in which the patient is the co-creator of their health (Bessant et al ., 2012; Nambisan and Nambisan, 2009; Ciasullo et al ., 2022) may alleviate the problem.…”
Section: Introductionmentioning
confidence: 99%